El clima laboral y el desempeño laboral del personal operativo de la empresa Sedalib S.A. 2015 - Alvarado Jaime, Heber Hely (2017)
The present thesis, entitled "The Labor Climate and the Labor Performance of the Operational Personnel of the Company Sedalib S.A."; Had as main problem to see how the Labor Climate influences the Performance of the operating personnel of the company Sedalib S.A. And aimed to determine the influence of the work climate on the performance of operational personnel. We worked with a sample universe of 196 operative workers, using the technique of the survey. The design used was the transectional descriptive. The work climate was evaluated taking into account the criteria of communication, needs and motivation, objectives and roles, integration, leadership, changes, working conditions, satisfaction and self-evaluation; And performance was assessed through the criteria of teamwork, results orientation, commitment and integrity. It was determined that the working climate in the company Sedalib S.A. Is good and that the performance is at a very good level, so it is concluded that the Labor Climate has a positive influence on Performance.